KINERJA PENYULUHAN DALAM PEMBERDAYAAN PETANI PADI DI KABUPATEN INDRAGIRI HILIR - Fiki Afrialfa; Rosnita Rosnita; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2019)
The objectives of the research are: (1) analyze the performance of extension workers from (Competence, Roles, Independence, and Social) (2) analyze the level of empowerment independence of farmer. The research conducted in Indragiri Hilir regency Kempas, Batang Tuaka and Keritang district. Samples taken with population and purposive sampling, with 156 independent smallholder sample from farmer group and 42 sample from agricultural extension. Data analysis used likert scale. Conclusion (1) The performance of extension worker who has been running in the field of rice farming business in Indragiri Hilir regency has been running